Anti-Citrullinated Cyclic Peptide Antibody and Functional Disability Are Associated With Poor Sleep Quality in Rheumatoid Arthritis - Shamala RAJALINGAM,; Rajalingham SAKTHISWARY,; Heselynn HUSSEIN, (Archives of Rheumatology, 2017)
Objectives: This study aims to determine the predictors of poor sleep quality in rheumatoid arthritis (RA). Patients and methods: This was a monocentric, cross sectional, case-control study which was conducted at the Putrajaya Hospital, Malaysia. We recruited 46 patients with RA (3 males; 43 females; mean age 48.15±14.96) and 46 age and sex-matched healthy controls (3 males; 43 females; mean age 47.11±12.22). RA patients were assessed for their disease activity based on disease activity score in 28 joints, disease damage based on radiographic erosions, and functional status based on Health Assessment Questionnaire Disability Index. The Pittsburgh Sleep Quality Index (PSQI) scores were determined by interviewing all the subjects. Subjects with RA were further subdivided based on their PSQI scores as “good sleepers” with PSQI scores of <5 and “poor sleepers” with PSQI scores of ≥5. Results: The percentage of poor sleepers was significantly higher among RA patients (47.83% versus 9.57%). Median scores of 5 out of 7 components of the PSQI were higher among RA patients compared to controls. Among poor sleepers with RA, a significantly higher proportion tested positive for anti-citrullinated cyclic peptide autoantibodies (p=0.037). Besides, poor sleepers had significantly higher median Health Assessment Questionnaire Disability Index (p=0.017) than good sleepers. However, both Health Assessment Questionnaire Disability Index (p=0.968) and anti-citrullinated cyclic peptide (p=0.431) were insignificant when entered in the equation of a logistic regression model. Conclusion: The findings of this study demonstrate a link between functional disability, anti-citrullinated cyclic peptide antibodies, and sleep quality in RA.